Phenotypic and genetic characteristics of patients with type 2 diabetes with different responses to metformin therapy in Novosibirsk region - Irina A. Bondar; Olesya Y. Shabelnikova; Ekaterina A. Sokolova; Olga V. Pyankova; Maksim L. Filipenko (Сахарный диабет)
Aim: The purpose of this study was to examine the phenotypic and genetic characteristics of patients with type 2 diabetes mellitus (T2DM) with different responses to treatment with metformin (MF) in the Novosibirsk region. Materials and methods: We examined 460 patients with T2DM in the Novosibirsk region. Patients were divided into groups according to their HbA1c level: patients who achieved the target HbA1c level during MF therapy (n = 209) and those who did not reach the target HbA1c level (n=251). Genotyping of ATM (rs11212617) was performed using polymerase chain reaction by TaqMan. Results: Patients who achieved the target HbA1c level during MF treatment (good response) were older (61. 1±9. 1 years vs. 57. 4±8. 4 years, p=0. 001), had later onset of diabetes (54. 6 ± 10. 1 years vs. 49. 2±8. 5 years, p = 0. 0001) and shorter duration of diabetes (6. 5±5. 9 years vs. 8. 2±6. 1 years, p=0. 03) compared with those who did not achieve the target HbA1c level. There was no statistically significant association between ATM rs11212617 and achieving the target HbA1c level among all patients [odds ratio (OR)=0. 94, 95% confidence interval = (0. 73–1. 23), p=0. 67] or those with MF monotherapy [OR=0. 90, (0. 65–1. 25), p=0. 54] or combination therapy [OR=1. 02, (0. 72–1. 43), p=0. 92]. There was an effect of age on response to MF therapy in all three groups (all patients: p=0. 001, MF monotherapy group: p=0. 04, combination therapy group: p=0. 0009). In the MF monotherapy group, low dose MF was associated with a good response (p=0. 03), and in the combination therapy group, males were more likely to have a good response (p=0. 003). Patients with genotype C/C or A/C for ATM (rs11212617) compared with those with genotype A/A were more likely to have high levels of triglycerides [2. 33 (1. 52–4. 2) mmol/l, 2. 09 (1. 35–3. 0) mmol/l and 1. 99 (1. 49–3. 21) mmol/l, respectively, p=0. 001], coronary heart disease (CHD) (13. 4%, 13. 4% and 9. 6%, respectively, p=0. 009) and myocardial infarction (7. 8%, 3. 2% and 4. 0%, respectively, p=0. 001). Conclusion: Patients with T2DM who had a good response to MF therapy were older, more likely to be male and had a later onset of T2DM. Genotype C/C for ATM rs11212617 was associated with high triglycerides, CHD and myocardial infarction. ATM rs11212617 was not associated with response to MF therapy in the Novosibirsk region.